IMPLEMENTASI KEBIJAKAN PENANGANAN DAN PENGENDALIAN CORONA VIRUS DISEASE-2019 PADA SEKTOR PARIWISATA DI KOTA TOMOHON - Steven Rudy Tampah; Maria Heni Pratiknjo; Very Yohanis Londa (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study was to analize the implementation of policies for handling and controlling covid-19 on the tourism sector in Tomohon City. The method used in this research is descriptive method using a qualitative approach. The research was conducted in Tomohon City using empirical data obtained through observations and interviews to 15 informants. The results showed that the implementation of policies for handling and controlling covid-19 on the tourism sector was carried out based on standards and policy targets through programs, namely physical distancing and work form home and the Tomohon City government program through the announcement of the mayor of Tomohon and Tomohon Mayor Regulation Number 28 of 2020 which is implemented based on the principles of implementing policies for handling and controlling covid-19 on the tourism sector in Tomohon City. In implementing this policy, communication factors between policy implementers, resources, disposition and bureaucratic structures are very influential in implementation. However, in implementing the policy, there are several weaknesses of these factors, namely the lack of communication between institutions, especially in the tourism sector, for example from the tourism office to the Indonesian Tourism Guides Association in Tomohon City, budget constraints, and lack of human resources as executors either as professionals or as professionals, tourism observers, especially on the tourism sector in the city of Tomohon.